Development of technology for obtaining electrodes based on copper wire using in the manufacture of solar modules - M. S. Illarionova; K. Y. Ivanova; M. V. Kuzmin; A. O. Patianova; V. L. Semenov (Chimica Techno Acta)
To optimize the technological process of manufacturing copper wire coated with solder of the POIN-52 grade, the optimal modes for the tinning temperature, linear velocity, diameter of the diamond die and flux were identified. It was found that the best wire tinning process is achieved when cleaning the surface of a copper wire by the method of electrochemical degreasing. The results of the tests showed that, in terms of mechanical and electrical parameters wire meets the require-ments for electrodes in the manufacture of solar modules. The results of climatic tests of solar modules  showed a high degree of reliability with a power loss of 0.86% and thermal cycling tests with a power loss of 0.4%, which is within tolerance.